2013
DOI: 10.1016/j.joca.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of cartilage defects, and other MRI findings with pain and function in individuals with mild–moderate radiographic hip osteoarthritis and controls

Abstract: Objective To evaluate the relationship of hip radiographic osteoarthritis (ROA) and MR findings of cartilage lesions, labral tears, bone marrow edema like lesions (BMEL) and subchondral cysts with self-reported and physical function. Design Eighty five subjects were classified as controls (n= 55, KL 0, 1) or having mild-moderate ROA (n = 30, KL 2, 3). T2-weighted MR images at 3-Tesla were graded for presence of cartilage lesions, labral tears, BMELs and subchondral cysts. Posterior wall sign, cross-over sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
84
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 47 publications
12
84
4
1
Order By: Relevance
“…Interestingly, of the included studies that reported acetabular and femoral cartilage defects independently, a trend highlighting a greater prevalence of acetabular cartilage defects was observed in symptomatic individuals. Our finding is consistent with studies reporting associations between acetabular cartilage damage and pain, clinical symptoms and reduction in function 74. The presence of cartilage defects could indicate early stages of the arthritic cascade, and the involvement of other tissues such as periarticular tissues, subchondral bone or synovial tissue 71 74 78 79…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, of the included studies that reported acetabular and femoral cartilage defects independently, a trend highlighting a greater prevalence of acetabular cartilage defects was observed in symptomatic individuals. Our finding is consistent with studies reporting associations between acetabular cartilage damage and pain, clinical symptoms and reduction in function 74. The presence of cartilage defects could indicate early stages of the arthritic cascade, and the involvement of other tissues such as periarticular tissues, subchondral bone or synovial tissue 71 74 78 79…”
Section: Discussionsupporting
confidence: 87%
“…The diagnosis of OA in canine patients is based upon history, physical exam and radiographic evidence. Finally, MRI findings reveal the changes of joint and cartilage degeneration consistent with OA [26][27][28][29][30].…”
Section: Anti-arthritic Efficacymentioning
confidence: 91%
“…The diagnosis of OA in canine patients is based upon history, physical exam and radiographic evidence. Finally, MRI findings reveal the changes of joint and cartilage degeneration consistent with OA [26][27][28][29][30].Canines with OA are treated with multipronged approaches, involving invasive as well as non-invasive measures. The objectives in managing OA include minimizing joint pain by reducing the inflammation and slowing the progression of the cartilage damage and thereby increasing the joint flexibility and quality of life.…”
mentioning
confidence: 99%
“…CT scan and/or MRI findings reveal changes of the joint and cartilage degeneration, which are consistent with OA, but are limited to humans and experimental studies [31][32][33].…”
Section: Introductionmentioning
confidence: 99%